Comparative omics analysis of a deep-sea barnacle species (Cirripedia, Scalpellomorpha) and shallow-water barnacle species provides insights into deep-sea adaptation - Mao, Ning; Shao, Wentai; Cai, Yuefeng; Kong, Xue; Ji, Nanjing; Shen, Xin (Frontiers in Marine Science, 2024)
Barnacles have demonstrated adaptability to a range of habitats, spanning from shallow water to the deep sea. Given the harsh conditions present in hydrothermal vents, hydrothermal vent barnacles serve as the model organism for investigating the interplay between evolution and adaptability. In order to gain insights into barnacle adaptive characteristics, particularly within hydrothermal vents, we conducted a comprehensive analysis of the mitogenomes and transcriptome in a deep-sea barnacle (Vulcanolepas fijiensis), in comparison to its shallow-water related species. The mitogenomes with the same genetic skews and the non-synonymous/synonymous mutation ratios (Ka/Ks) of the mitogenomes indicate that the protein-coding genes (COIII, ND2, and ND6) of V. fijiensis are under positive selection. Meanwhile, the functional annotation shows that distinctly positive selected orthologs in V. fijiensis are predominately related to neural signal transduction, immunity, antiapoptotic, and energy metabolism. These results indicate that the mitogenomes and key genes found in transcriptomic analysis are under high-temperature and high-pressure conditions, and which may contribute V. fijiensis to have evolved to adapt to the extreme hydrothermal vent environments. The findings shed light on the mitogenome and transcriptome of V. fijiensis, which lays a foundation for the in-depth understanding of the adaptation mechanism of sessile invertebrates to the deep-sea environment.